Pengembangan Kurikulum Berbasis Kearifan Lokal Pranata Mangsa pada Mata Pelajaran PIPAS Kelas X: Strategi Adaptasi Petani dan Sistem Ekonomi Agraris - Tarso Sarwono; Aviv Eka Fajarian Saputro; Eko Winarto; Heru Suprapto; Anip Dwi Saputro (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Global climate change significantly impacts the uncertainty of planting seasons in Indonesia, particularly in Java. This study aims to develop a curriculum based on the local wisdom of Pranata Mangsa for the PIPAS subject (Project-Based Learning of Social Sciences) in Grade X, focusing on farmers' adaptation strategies and the agrarian economic system. The method employed is curriculum analysis using an ethnoscience approach and Project-Based Learning (PjBL) design. The development outcome is a curriculum framework that includes basic competencies, achievement indicators, learning materials, and student project activities. This curriculum integrates traditional Pranata Mangsa knowledge with modern climate data from the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) to produce contextual, critical, and relevant learning. The curriculum covers four main topics: an introduction to Pranata Mangsa, traditional farmers' adaptation strategies, the agrarian economic system, and the impact of climate change on traditional planting calendars. Assessment is conducted through project report rubrics, presentations, written tests, and attitudinal evaluations. This curriculum is expected to help students understand farmers' adaptation to climate change, develop critical thinking skills, and preserve local cultural heritage as part of the Merdeka Curriculum's vision for project-based learning with local wisdom themes.